Pengaruh Kompetensi dan Person-Organization Fit Terhadap Kinerja Karyawan dengan Komitmen Organisasi Sebagai Variabel Intervening - Sri Margono; Sutianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to verify in depth the impact of organizational commitment and organizational commitment of Boyolali regional financial agency employees. Data for this study was collected by distributing questionnaires to 48 respondents. The research examines how competency and organizational performance affect employee performance at the Boyolali District Regional Financial Agency, considering organizational commitment as a mediator. The research design uses a quantitative methodology to establish causal relationships among the studied variables. Smart-PLS was employed for data analysis, which involved testing the outer model, inner model, and hypotheses. The results of this study reveal that individual competence and person-organization fit do not have a statistically significant impact on employee performance. In contrast, organizational commitment shows a significant positive effect on employee performance. Additionally, both competence and person-organization fit contribute substantially to enhancing organizational commitment. Mediation analysis confirms that organizational commitment significantly mediates the relationship between competence, person-organization fit, and employee performance.